A great auk for the Sun King. Issue 1 (April 2016) - De Lozoya, Arturo Valledor; García, David González; Parish, Jolyon
Abstract : This paper describes two watercolours and one engraving of the great auk ( Pinguinus impennis ) executed by the French painter Nicolas Robert probably between 1666 and 1670. Despite their interest as early images of this extinct species and the first ones rendered in colour, they have not been mentioned in the literature. The images suggest that the bird was kept alive in the menagerie at the palace in Versailles, where Robert portrayed it for Louis XIV; Robert's paintings are collectively known as "Les vélins du Roi".